2014
DOI: 10.4238/2014.january.22.10
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance analysis of bacterial strains isolated from burn patients

Abstract: ABSTRACT.This study aimed to analyze the spectrum and drug resistance of bacteria isolated from burn patients to provide a reference for rational clinical use of antibiotics. Up to 1914 bacterial strain specimens isolated from burn patients admitted to hospital between 2001 and 2010 were subjected to resistance monitoring by using the K-B paper disk method. Retrospective analysis was performed on drug resistance analysis of burn patients. 9727-9734 (2014) resistance, respectively. Antibacterial drugs that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…A study by Behzadnia, S., et al is agree with this result [6]. But a study by Wang, L.F., and his coauthors found that A. baumannii is the most common bacterial cause infection in burn patients [23]. The factor which may be lead to the presence of much Acinetobacter on a normal skin commensal and upper respiratory airway and it spreads easily [24].…”
Section: Bacteriological Infectionssupporting
confidence: 68%
See 1 more Smart Citation
“…A study by Behzadnia, S., et al is agree with this result [6]. But a study by Wang, L.F., and his coauthors found that A. baumannii is the most common bacterial cause infection in burn patients [23]. The factor which may be lead to the presence of much Acinetobacter on a normal skin commensal and upper respiratory airway and it spreads easily [24].…”
Section: Bacteriological Infectionssupporting
confidence: 68%
“…A previous study by Wang, L.F., and his coauthors demonstrated that the drug resistant to A. baumannii due to easily produce drug resistance by combining plasmid. A variety of resistant plasmids coexist, such as plasmid-mediated TEM-1 and TEM-2, TEM-2 β-lactamase, and chromosome-mediated β-lactamase; the change in penicillin-binding proteins and the permeability decrease of outer membrane proteins and also result drug resistance [23].…”
Section: Antibacterial Sensitivity Isolatesmentioning
confidence: 99%
“…It has been proved that skin wounds are susceptible to infections caused by gram-positive bacteria like Staphylococcus aureus, and gram-negative bacteria like Escherichia coli, Pseudomonas aeruginosa [1]. Infection of wound surfaces often causes delayed healing or nonhealing of the wound, which results in mortality [2].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, during recent decades the widespread use of antibiotics led to the emergence of drug-resistant bacteria, such as multidrug and extensively drugresistant organisms. Thus in that area, precise knowledge of the bacterial resistance patterns is essential for determining the best antibiotic regimens or empirical therapy in critical conditions, for treatment of burn patients [1].…”
Section: Introductionmentioning
confidence: 99%